The Implementation of Critical Reading in Teaching Reading Comprehension at SMAN 10 Pangkep - Veranda Amir; Radiah Hamid; Nurdevi Bte Abdul (FKIP - Universitas Riau, 2026)
This study examines the implementation of critical reading in teaching reading comprehension and identifies the challenges faced by English teachers at SMAN 10 Pangkep. Using a descriptive qualitative design, the study involved two English teachers, with data collected through lesson plan analysis, classroom observations, and interviews. The data were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that the implementation of critical reading remains limited and is primarily focused on lower-order thinking skills. Teachers tend to apply pre-reading strategies such as skimming and predicting; however, higher-order thinking strategies, including annotating and contextualizing, are rarely implemented. As a result, classroom instruction remains procedural and text-oriented, with students positioned as passive recipients of information. The study also reveals several challenges, including students’ limited vocabulary as a cognitive barrier, passive learning culture influenced by fear of making grammatical errors as a sociocultural barrier, and misalignment between curriculum and assessment practices as a systemic barrier. It can be concluded that critical reading has not yet been effectively integrated into classroom practice.